Спрямування заходів вторинної профілактики серцево-судинних уражень у хворих на цукровий діабет 2-го типу - Приступюк, О. М. (Clinical Endocrinology and Endocrine Surgery, 2012)
Analyzing the risk factors for cardiovascular lesions in patients with type 2 diabetes one can consider deficiency of compensation of diabetes as the leading risk factor for cardiovascular abnormalities. This is followed by an excess of weight, hypertension and dyslipidemia.